UNDERSTANDING THE MECHANISM OF SEASONAL UPWELLING AND DOWNWELLING AT THE SOUTHERN COAST OF MAKASSAR STRAIT - Muhammad Arief Wibowo; Ivonne M Radjawane; Ibnu Sofian (Berkala Perikanan Terubuk, 2020)
The mechanism of temporary upwelling and downwelling in the southern coast off Makassar Strait, Indonesia is determined not only by the wind-driven coastal during southeast monsoon (SEM) and northwest monsoon (NWM) but also by meeting of two current systems based on previous research. During SEM, water mass of the Flores Sea in eastern area meets the throughflow water coming from northern of Makassar Strait and flow together to Java Sea and this causes upwelling occur. But during NWM, water mass of the Java Sea western   area meets the through flow water and flow together to southern cost of Celebes Island and causes downwelling occur.  The first mechanism is well proven but the second one need more investigation.Twenty years of data result obtained from numerical simulation over the Makassar Strait and adjacent waters are used to describe the seasonal characteristic and mechanism of upwelling in this region. The 3D baroclinic ROMS (Regional Ocean Model System) from Rutgers version was simulated from 1995 to 2014.The climatological results show the existing of upwelling and downwelling clearly identified by the decreasing or increasing of sea surface temperature ± 2ºC and also increasing or decreasing of surface salinity ±0.5 Psu compared by surrounding waters. The evidence of upwelling starts on June, maximum intensity in August and disappears on September following the easterly wind during southeast monsoon. But downwelling start on   December, maximum intensity in January and disappears on February. The mixed layer depth becomes shallow and there is an uplift water from the thermocline to the surface at the upwelling occur, but when downwelling occur the mixed layer depth becomes deeper. The instability of water column was detected from the Brunt-Väisälä frequency (N2) and Richarson number (Ri). By calculating the vorticity and investigate the current circulation we detect the eddy formation in southern part of the Celebes Island at Java Sea and Flores Sea and suggested due to the meeting of current system. We found the Ekman transport is moving to the southern direction offshore of Celebes Island and produces the upwelling during SEM. But when NWM occur, Ekman transport is moving to the northern direction from offshore to the Celebes Island and produce downwelling.